STUDYING NEW METHODS OF ORGAN-SAVING OPERATIONS FOR AMPULARY RECTAL CANCER - Uktam M. Kurbankulov; Hasan I. Mamajonov (Scholar Express Journals, 2023)
A number of scientific studies are being conducted all over the world to optimize the morphological and clinical basis for performing organ-preserving surgical interventions for ampullary rectal cancer. In this regard, of particular importance are scientific studies aimed at developing the morphological basis of unsatisfactory results of organ-preserving surgical interventions for cancer of the ampullary rectum, instructions for performing organ-preserving surgical interventions for malignant tumors of the ampullary rectum, taking into account morphological features, performing organ-preserving surgical interventions for cancer of the ampullary rectum with varying degrees of differentiation.
Keywords: Ampullary rectal cancer; malignant neoplasms; research methods